Development of Handout Android-Based Application on Buffer Solution using Discovery Learning Model - Agustina Agustina; Army Auliah; Hardin Hardin (Universitas Negeri Medan, 2023)
Research and development aims to produce Handout Buffer Solution on a quality Android Application. Quality is seen based on the validity, practicality, and effectiveness. Based Buffer Solution Handout Refers to the ADDIE (Analysis, Design, Development, Implementation, and Evaluate) development model. The instruments used for validity are validation sheets by theory experts and media experts, practicality teacher response questionnaires and students, and the effectiveness of the learning outcomes test. The results of the research show: 1) the validity of the Handout from the theory expert 3.65 and the media expert 3.58 with a very valid category, 2) the average percentage of practicality of the handout based on the teacher's response questionnaire equal to 91% and 87.58% of students in the very practical category, 3) the valid handouts that fulfill the effective criteria (≥ 85%) based on the achievement of class completeness with a percentage of 86.1 %. Thus, it can be concluded that the Handout Buffer solution Based on Android Application development with the ADDIE Model is very valid, very practical, and effective for use in the learning process.